Rural women entrepreneurship: constraints and strategies - Govindappa, G.T. (1999)
The individual is one of the very important factors in entrepreneurship. The individuals with high-need for achievement become entrepreneurs. Entrepreneurship development among rural women should first prepare them through motivation training for entrepreneurial venture. Rural women also face social and technological risks. Strategy for development of entrepreneurship among these women should address these risks also. - Reproduced
Keywords: Entrepreneurs - India; Rural women - India; Women in business - India; Women in business